Respostas

A melhor resposta!
2014-02-15T18:51:50-02:00
A)  \left \{ {{x + y = 8} \atop {x - y = 4}} \right.
    2x = 12         ---> x + y = 8
    x = 6                   6 + y = 8
                                  y = 2

b)  \left \{ {{x + y = 6} \atop {x - y = 8}} \right.
    2x = 14        ----> x + y = 6
      x = 7                7 + y = 6
                                 y = - 1

c)   \left \{ {{2x + 3y = -10} \atop {x - y = 0}} \right
.
multiplicando x - y = 0 por ( - 2) fica:  \left \{ {{2x - 3y = -10} \atop {-2x + 2y = 0}} \right.  
 y = -10   ----> 2x - 3y = -10
                     2x - 3 . (-10) = -10
                      2x + 30 = -10
                         2x = -10 - 30
                           2x = - 40
                             x = - 20


creio que seja assim. espero ter ajudado ;)
2 5 2